2018
DOI: 10.12944/crnfsj.6.3.19
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Enzymatic Browning by Onion (Allium cepa L.): Investigation on Inhibitory Mechanism and Identification of Active Compounds

Abstract: Presence of browning or black-spot in fresh foods can adversely affect consumer acceptance. Onion has been reported to exert inhibitory activity against browning reaction. This research aimed to uncover the mechanism and identify active compounds in onion responsible for PPO inhibitors based on metabolomic approach. Onion was fractioned using different solvents, i.e n-hexane; chloroform; ethyl acetate; water, respectively. As a result, ethyl acetate fraction (EAF) of the onion demonstrated the strongest inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…Browning of agro-products can lead to the deterioration of product quality and nutritional value, resulting in a decrease in consumer acceptance. Onion has been demonstrated to possess an inhibitory activity against the enzymatic browning reaction in fresh foods, such as fruit juice, mushrooms, and potato slices (187)(188)(189)(190). In addition, intake of onion juice was reported to exhibit a beneficial effect on bone loss and bone mineral density by improving antioxidant capacity (57).…”
Section: Other Health Functions Of Onionmentioning
confidence: 99%
“…Browning of agro-products can lead to the deterioration of product quality and nutritional value, resulting in a decrease in consumer acceptance. Onion has been demonstrated to possess an inhibitory activity against the enzymatic browning reaction in fresh foods, such as fruit juice, mushrooms, and potato slices (187)(188)(189)(190). In addition, intake of onion juice was reported to exhibit a beneficial effect on bone loss and bone mineral density by improving antioxidant capacity (57).…”
Section: Other Health Functions Of Onionmentioning
confidence: 99%
“…This enzyme is a copper-containing oxidoreductase catalyzing the oxidation of phenolic compounds and consequently leads to the deterioration of antioxidants and colour change of herbal foodstuffs during the processing [94]. Yuniarti et al (2018) identified several phenolic inhibitors of PPO, including kaempferol, quercetin, and cyanidin in onion [95]. In addition, catechins, constituting a vast majority of TPC found in tea, act as a PPO competitive inhibitor because of their similarity to the substrate of PPO.…”
Section: Enzymatic Browningmentioning
confidence: 99%
“…A well‐known mechanism displayed by MRPs. In addition, the hydroxyl groups could bind active site of PPO, changing the enzyme's native conformation, thus losing its activity (Yuniarti et al, 2018). Evidently, glucose‐lysine and glucose‐arginine models systems known to produce FL and AF Amadori rearrangement products were found to inhibit banana PPO during a 10‐day storage (Lee, 2007).…”
Section: Formation Of Mrps In Heated Plant Extractsmentioning
confidence: 99%